Analysis of Immune Response Markers in Jorge Lobo's Disease Lesions Suggests the Occurrence of Mixed T Helper Responses with the Dominance of Regulatory T Cell Activity - Azevedo, Michelle de C. S.; Rosa, Patricia S.; Soares, Cleverson T.; Fachin, Luciana R. V.; Baptista, Ida Maria F. D.; Woods, William J.; Garlet, Gustavo P.; Trombone, Ana Paula F.; Belone, Andrea de F. F. (PLOS ONE, 2015)
Jorge Lobo’s disease (JLD) is a chronic infection that affects the skin and subcutaneous tissues. Its etiologic agent is the fungus Lacazia loboi. Lesions are classified as localized, multifocal, or disseminated, depending on their location. Early diagnosis and the surgical removal of lesions are the best therapeutic options currently available for JLD. The few studies that evaluate the immunological response of JLD patients show a predominance of Th2 response, as well as a high frequency of TGF-β and IL-10 positive cells in the lesions; however, the overall immunological status of the lesions in terms of their T cell phenotype has yet to be determined. Therefore, the objective of this study was to evaluate the pattern of Th1, Th2, Th17 and regulatory T cell (Treg) markers mRNA in JLD patients by means of real-time PCR. Biopsies of JLD lesions (N = 102) were classified according to their clinical and histopathological features and then analyzed using real-time PCR in order to determine the expression levels of TGF-β1, FoxP3, CTLA4, IKZF2, IL-10, T-bet, IFN-γ, GATA3, IL-4, IL-5, IL-13, IL-33, RORC, IL-17A, IL-17F, and IL-22 and to compare these levels to those of healthy control skin (N = 12). The results showed an increased expression of FoxP3, CTLA4, TGF-β1, IL-10, T-bet, IL-17F, and IL-17A in lesions, while GATA3 and IL-4 levels were found to be lower in diseased skin than in the control group. When the clinical forms were compared, TGF-β1 was found to be highly expressed in patients with a single localized lesion while IL-5 and IL-17A levels were higher in patients with multiple/disseminated lesions. These results demonstrate the occurrence of mixed T helper responses and suggest the dominance of regulatory T cell activity, which could inhibit Th-dependent protective responses to intracellular fungi such as L. loboi. Therefore, Tregs may play a key role in JLD pathogenesis.